Faktor-Faktor yang Berhubungan dengan Stres Kerja pada Perawat di Rumah Sakit X Kabupaten Bogor Tahun 2024: Factors Associated with Work Stress Among Nurses at Hospital X, Bogor Regency, in 2024 - Panjaitan, Dewi Ulina; Budi Yulianto; Astrid Novita (MPI Press, 2025)
Introduction: Job stress is a feeling of pressure felt by employees in relation to their work as a result of an imbalance between individual characteristics and job demands and the environment which has an impact on the employee's behavior and physical and psychological condition. Objectives: The aim of the research is to determine the factors related to work stress among nurses at Hospital X, Bogor Regency in 2024. Method: The approach used in data analysis for this research uses a quantitative approach using a cross-sectional design. Result: The gender variable from the statistical test results obtained a p value of 0.356 with an OR value of 0.455, the age variable from the statistical test results obtained a p value of 0.005, the education variable from the statistical test results obtained a p value of 0.008, the length of service variable from the statistical test results obtained a p value of 0.003, the wage or income variable from the statistical test results obtained a p value of 0.008, the workload variable from the statistical test results obtained a p value of 0.001 with. There is a relationship between work stress and age, education, length of service, wages or income, and workload in nurses at Hospital X, Bogor Regency, but the gender variable is not related to work stress in nurses at Hospital X, Bogor Regency. Conclution: There is a relationship between work stress and age, education, length of service, wages or income, and workload for nurses at Hospital X Bogor Regency, but the gender variable is not related to work stress for nurses at Hospital X Bogor Regency.